2014
DOI: 10.1186/1472-6831-14-92
|View full text |Cite
|
Sign up to set email alerts
|

Self-induced vomiting and dental erosion – a clinical study

Abstract: BackgroundIn individuals suffering from eating disorders (ED) characterized by vomiting (e.g. bulimia nervosa), the gastric juice regularly reaches the oral cavity, causing a possible risk of dental erosion. This study aimed to assess the occurrence, distribution and severity of dental erosions in a group of Norwegian patients experiencing self-induced vomiting (SIV).MethodsThe individuals included in the study were all undergoing treatment at clinics for eating disorders and were referred to a university dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
68
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 34 publications
5
68
1
6
Order By: Relevance
“…Otsu et al [16] did not note dental erosion in 14% of the vomiting patients. The above data shows that erosive lesions are due to numerous factors and the cavities are a consequence of the interactions between them all [14,20].…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…Otsu et al [16] did not note dental erosion in 14% of the vomiting patients. The above data shows that erosive lesions are due to numerous factors and the cavities are a consequence of the interactions between them all [14,20].…”
mentioning
confidence: 75%
“…Hermont et al [19] found erosion in 45% of the people affected, contrary to the healthy individuals in whom 8.8% had such lesions. Still, Uhlen et al [20] noted erosion in nearly 70% of patients affected with eating disorders. It must be emphasized that the incidence of erosion varies in the group of patients with such an entity and is related to the type of a disorder.…”
mentioning
confidence: 99%
See 3 more Smart Citations